Care in crises: Nursing and humanitarian aid. Issue 7 (July 2018) - Freeman, Anna
Abstract : A nurse shares how her experiences working in the field with Doctors Without Borders opened her eyes to the challenges and rewards of delivering high-quality healthcare in extremely difficult circumstances.